2021
DOI: 10.20944/preprints202102.0188.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bio-Gasoline and Bio-Kerosene Production by Fractional Distillation of Pyrolysis Bio-Oil Açaí Seeds

Abstract: The bio-oil obtained by pyrolysis of Açaí (Euterpe oleracea Mart.) seeds at 450 ºC, 1.0 atmosphere, in technical scale, submitted to fractional distillation to produce biofuels-like fractions. The distillation of bio-oil carried out in a laboratory distillation column (Vigreux) of 30 cm. The physical-chemistry properties (density, kinematic viscosity, acid value and refractive index) determined by official methods. The chemical functions present in distillation fractions determin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…These results were effectively modeled using a first-order exponential growth model, with an r 2 value of 1.00 for both categories. These findings align with the research conducted by de Sousa et al [32], who investigated the influence of process temperature on the concentration of hydrocarbons and oxygenates in bio-oil derived from Açaí seeds using a pilotscale pyrolysis setup. Their study, which examined temperatures of 350, 400, and 450 °C under a pressure of 1.0 atm, demonstrated that the concentration of hydrocarbons increased while the concentration of oxygenates decreased with rising temperature.…”
Section: Effect Of Process Temperaturesupporting
confidence: 91%
See 4 more Smart Citations
“…These results were effectively modeled using a first-order exponential growth model, with an r 2 value of 1.00 for both categories. These findings align with the research conducted by de Sousa et al [32], who investigated the influence of process temperature on the concentration of hydrocarbons and oxygenates in bio-oil derived from Açaí seeds using a pilotscale pyrolysis setup. Their study, which examined temperatures of 350, 400, and 450 °C under a pressure of 1.0 atm, demonstrated that the concentration of hydrocarbons increased while the concentration of oxygenates decreased with rising temperature.…”
Section: Effect Of Process Temperaturesupporting
confidence: 91%
“…al. [32]. The concentration of oxygenates in bio-oil were correlated with a first order exponential decay model, exhibiting in all the cases root-mean-square error (r 2 ) of 1.00.…”
Section: Effect Of Process Temperaturementioning
confidence: 93%
See 3 more Smart Citations